Vertical Variations of Submesoscale Motions Between New Jersey Shelf and Bermuda - Li, Jianing; Wang, Xin (Frontiers in Earth Science, 2022)
Based on the measurements from Oleander Project, the behaviors of submesoscale motions are examined in the area between New Jersey Shelf and Bermuda. The vertical variation of Rossby number, kinetic energy in submesoscale range and the power law of kinetic energy spectra suggest that submesoscale motions are mainly confined within the surface mixed layer with seasonality that strong in winter and weak in summer. Besides, submesoscale motions with no significant seasonality were also found beneath the surface mixed layer, which could reach 500 m depth. A possible explanation is that the drastically varying flows in the Gulf Stream and mesoscale eddies periphery could generate strong lateral shear throughout their influence depth, which is favorable of breaking the geostrophic balance and causing submesoscale motions beneath the surface mixed layer.